论汉魏六朝挽歌与悼亡诗的生死主题 = Theme on life and death in elegy and lament poetry of Han, Wei and six dynasties - 郑慧萍 Teh, Hui Ping (2014)
汉魏六朝在中国历史上属于特殊时期。政局动荡不安，个人主义逐渐兴起，玄学逐渐流行，形成社会变迁，这些深刻影响文学作品。政权不断更替，仕人的生命朝不保夕。仕人济济于功名利禄，但是担心自身安危，因此效仿庄周淡然看待死亡，以调剂恐惧，由此产生挽歌和悼亡诗。挽歌和悼亡诗结合诗人仕途，通过不同途径探讨生死主题。挽歌中的场景也是他人哀悼亲友的空间。挽歌通过第一人称的叙述角度感叹时间漫长、惋惜生命消逝以及增添乐趣与减轻痛苦。同时，它在哲学领域上思考生死。悼亡诗则反映了诗人的情感世界以及他们对亡妻的哀悼情感。正文分为四章，为本文重点。一章理清挽歌和悼亡诗的定义与流变、点出挽歌和悼亡诗的共性及他们与其他文体的区别，再探讨生死主题产生的原因及内涵。二章探讨挽歌的空间、叙述角度和生死观。三章讨论悼亡诗中的夫妻情感、直述哀伤和孤独情怀以及超越季节的哀悼。最后作出挽歌和悼亡诗的比较和文学史意义。Han Wei and Six Dynasties is a special period in ancient China which involves warfare and conflict. Individualism surges and different school of thoughts such as Neo-Daoism emerged, contributing to radical changes in society. These social upheavals are reflected in literature works. During this time, poets risk death when they engage in politics due to political instability. Risking lives and limbs, poets embark on political paths seeking wealth and fame, yet hoping to alleviate their fear of death, adopt Zhuangzi’s calm attitude towards death. Elegies and laments are formed in this context. Elegies and laments explore themes on death and life through different means. At the same time, they incorporate poets’ political paths and feelings. Spaces are another form of avenue for people to express their feelings towards the deceased. Through the usage of first person narration, elegies express poets’ sighs at long duration of time, regret the loss of life and their hope for joy and pain reduction. It also reflects their philosophical views on life and death. Laments reflect poets’ emotional world and express their sorrowful feelings towards their deceased wives. This paper is divided into four chapters. The first chapter explores definitions and developments of elegies and laments, their similarities and differences which set them apart from other similar texts. Next, it explores reasons and definitions of theme on life and death in Han Dynasty and Six Dynasties. The second chapter deals with spaces, mode of narration and theme on life and death in elegies. The third chapter further explores relations between couples, sadness, isolation and sorrow that transcends seasons in laments. Lastly, it sums up comparison of elegies and laments and their literary significance.